Facilitated referral pathway for genetic testing at the time of ovarian cancer diagnosis: uptake of genetic counseling and testing and impact on patient-reported stress, anxiety and depression - Frey, Melissa K.; Lee, Sarah S; Gerber, Deanna; Schwartz, Zachary P.; Martineau, Jessica; Lutz, Kathleen; Reese, Erin; Dalton, Emily; Olsen, Annie; Girdler, Julia; Pothuri, Bhavana; Boyd, Leslie; et al. (Gynecologic oncology, 2020)
Timely genetic testing at ovarian cancer diagnosis is essential as results impact front line treatment decisions. Our objective was to determine rates of genetic counseling and testing with an expedited genetics referral pathway wherein women with newly-diagnosed ovarian cancer are contacted by a genetics navigator to facilitate genetic counseling. Patients were referred for genetic counseling by their gynecologic oncologist, contacted by a genetics navigator and offered appointments for genetic counseling. Patients completed quality of life (QoL) surveys immediately pre- and post-genetic assessment and 6 months later. The primary outcome was feasibility of this pathway defined by presentation for genetic counseling. From 2015 to 2018, 100 patients were enrolled. Seventy-eight had genetic counseling and 73 testing. Median time from diagnosis to genetic counseling was 34 days (range 10–189). Among patients who underwent testing, 12 (16%) had pathogenic germline mutations (BRCA1-7, BRCA2-4, MSH2-1). Sixty-five patients completed QoL assessments demonstrating stress and anxiety at time of testing, however, scores improved at 6 months. Despite the pathway leveling financial and logistical barriers, patients receiving care at a public hospital were less likely to present for genetic counseling compared to private hospital patients (56% versus 84%, P = 0.021). Facilitated referral to genetic counselors at time of ovarian cancer diagnosis is effective, resulting in high uptake of genetic counseling and testing, and does not demonstrate a long term psychologic toll. Concern about causing additional emotional distress should not deter clinicians from early genetics referral as genetic testing can yield important prognostic and therapeutic information. •Facilitated referral to genetic counselors resulted in high uptake of genetic counseling and testing.•Genetics referral at time of ovarian cancer diagnosis did not demonstrate a long term psychologic toll.•Despite leveling of financial barriers, patients at the public hospital were less likely to present for genetic counseling.•Ashkenazi Jewish patients reported higher levels of stress, anxiety and depression at time of genetic counseling.